2007
DOI: 10.1086/519812
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of European Merger Control: Evidence using Stock Market Data

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 30 publications
3
112
1
5
Order By: Relevance
“…In other words, ceteris paribus, cases filed to the DOJ are not the ones that lead to higher welfare losses. This result is in the same vein of the public choice school; antitrust policy goal is not linked to the economist's conception of social welfare (McChesney et Shughart II, 1995 9 Three variables of the U.S. Merger Guidelines appeared significant: barriers to entry, collusion, and efficiency gains. They showed efficiency considerations over the period didn't affect the authority's decision to accept or block a merger.…”
Section: Different Approaches To Assessing An Antitrust Authoritymentioning
confidence: 79%
See 1 more Smart Citation
“…In other words, ceteris paribus, cases filed to the DOJ are not the ones that lead to higher welfare losses. This result is in the same vein of the public choice school; antitrust policy goal is not linked to the economist's conception of social welfare (McChesney et Shughart II, 1995 9 Three variables of the U.S. Merger Guidelines appeared significant: barriers to entry, collusion, and efficiency gains. They showed efficiency considerations over the period didn't affect the authority's decision to accept or block a merger.…”
Section: Different Approaches To Assessing An Antitrust Authoritymentioning
confidence: 79%
“…However, if the authority intervenes, the market anticipates a more costly operation when the acquirer is a nonEuropean firm. Another example is Duso et al (2003) who used event study analysis of stock data to evaluate European merger control in terms of political economy. They found that the protection of consumer surplus was not the only motive of the EC : The institutional and political environment did matter.…”
Section: Different Approaches To Assessing An Antitrust Authoritymentioning
confidence: 99%
“…The basic insight behind this categorization of mergers is that transactions which enhance collusion (or market-power) will increase the underlining value and profitability of competitor firms on average, while mergers which enhance efficiencies (or true synergies) will decrease the underlining value and profitability of competitor firms on average (Duso et al, 2007(Duso et al, , 2011(Duso et al, , 2013.…”
Section: Empirical Demonstrationmentioning
confidence: 99%
“…With these measures at hand, we follow Duso et al (2007Duso et al ( , 2011Duso et al ( , 2013 in operationalizing our merger typology.…”
Section: Mcwilliams and Siegel 1997)mentioning
confidence: 99%
“…A different approach is to evaluate the reaction of non-merging firms (Dafny (2009) and Duso et al (2007 and2013)). For example, Gugler and Szuecs (2016) investigate whether mergers exert profit externalities on competitors.…”
Section: Introductionmentioning
confidence: 99%